2021
DOI: 10.1038/s12276-021-00613-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferases: promising targets for cancer therapy

Abstract: Protein methylation, a post-translational modification (PTM), is observed in a wide variety of cell types from prokaryotes to eukaryotes. With recent and rapid advancements in epigenetic research, the importance of protein methylation has been highlighted. The methylation of histone proteins that contributes to the epigenetic histone code is not only dynamic but is also finely controlled by histone methyltransferases and demethylases, which are essential for the transcriptional regulation of genes. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 247 publications
0
107
0
Order By: Relevance
“…This posttranslational modification is mainly catalyzed by the protein arginine methyltransferase (PRMT) family. PRMTs, composed of nine members, can be divided into three types (I, II and III) based on their catalytic activity: type I PRMTs (PRMT1, 2, 3, 4, 6, and 8) are responsible for asymmetric dimethylarginine (ADMA) and monomethylarginine (MMA), type II PRMTs (PRMT5 and 9) generate symmetric dimethylarginine (SDMA) and MMA, and type III PRMT (PRMT 7) catalyze the formation of MMA 6 , 7 . Since the dysregulation of protein arginine methylation is closely related to the development of cancer, PRMTs, as novel anticancer drug development targets, have attracted increasing attention 6 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This posttranslational modification is mainly catalyzed by the protein arginine methyltransferase (PRMT) family. PRMTs, composed of nine members, can be divided into three types (I, II and III) based on their catalytic activity: type I PRMTs (PRMT1, 2, 3, 4, 6, and 8) are responsible for asymmetric dimethylarginine (ADMA) and monomethylarginine (MMA), type II PRMTs (PRMT5 and 9) generate symmetric dimethylarginine (SDMA) and MMA, and type III PRMT (PRMT 7) catalyze the formation of MMA 6 , 7 . Since the dysregulation of protein arginine methylation is closely related to the development of cancer, PRMTs, as novel anticancer drug development targets, have attracted increasing attention 6 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The drug mechanism responsible for CARM1 inhibition has not yet been defined, and there is the possibility that it acts indirectly via the inhibition of HSP90, which was identified as a CARM1 interactor (EP 3 208 615 B1). In addition, we also indicated highly selective inhibitors of CARM1, recently developed and tested in experimental models [62][63][64]. PEITC is an organosulfur bioactive compound, known as an MAPK1 activator, that is currently in trial for lung cancer and leukemia treatment (NCT00691132 and NCT00968461).…”
Section: Discussionmentioning
confidence: 96%
“…The reactions catalyzed by PRMT1 are crucial for maintaining cellular health, and dysregulated PRMT1 contributes to the pathology of several cancers ( 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ). In this study we identified three mechanistically relevant dimer arm mutations by screening mutations that occur in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme targets numerous proteins involved in epigenetic and transcriptional regulation such as histone H4 ( 17 , 18 ), the estrogen receptor ( 19 , 20 ), and the progesterone receptor ( 21 ). Upregulation of PRMT1 is observed in many cancer types and often correlates with cancer grade and poor patient prognosis ( 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ), and there are a growing number of studies suggesting that PRMT1 is an important regulator in many pathways that are dysregulated in cancers ( 14 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ). While it is clear that PRMT overexpression is deleterious in many diseases, it is also clear that maintaining some level of arginine methylation is critical for cellular and organismal health.…”
mentioning
confidence: 99%